2012
DOI: 10.1016/j.jfoodeng.2011.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of a nanomultilayer coating of pectin and chitosan – Evaluation of its gas barrier properties and application on ‘Tommy Atkins’ mangoes

Abstract: A nanomultilayer coating made of food-grade, bio-based materials (consisting of five nanolayers of pectin and chitosan) was produced. This coating was firstly characterized in terms of the water vapor, oxygen and carbon dioxide permeabilities; these parameters exhibited values of 0.019 ± 0.005 Â 10 À11 , 0.069 ± 0.066 Â 10 À14 and 44.8 ± 32 Â 10 À14 g m/(Pa s m 2), respectively, and are of the same order of magnitude of those found in other nanomultilayer systems. The nanomultilayer system was applied on whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 52 publications
4
59
1
6
Order By: Relevance
“…Supporting this study results, Medeiros et al (2012) indicated that mangos coated with pectin and chitosan had better appearance and lower physiological loss than fruits from control group. One of the reasons for appearance change after harvest is the physiological loss due to transpiration, which may cause fruits to wilt, making them unattractive in market.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…Supporting this study results, Medeiros et al (2012) indicated that mangos coated with pectin and chitosan had better appearance and lower physiological loss than fruits from control group. One of the reasons for appearance change after harvest is the physiological loss due to transpiration, which may cause fruits to wilt, making them unattractive in market.…”
Section: Resultssupporting
confidence: 83%
“…Medeiros et al (2012) coated "Tommy Atkins" mangos with chitosan and pectin coating, kept for 45 days at 4°C and 90% of RH, and observed less physiological loss at 28 days to coated fruits. Cissé et al (2015) also had lower physiological loss as compared to control treatment fruits in mango fruits from Kent cultivar stored for 8 days coated with 1 and 1.5% chitosan.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations